Identificación y evaluación de riesgos psicosociales utilizando el método istas 21, a los trabajadores del área de reciclaje de la planta industrial Novacero S.A. (Latacunga) en el periodo 2012. - Beltrán Jaramillo, Juan Carlos (2013)
This thesis aims to deal a theoretical and practical way about factors of psychosocial risks that affects workers where the primary objective is to reduce the problems of occupational safety and health present in enterprises. It could do through evaluation of psychosocial risks using the method view ISTAS 21. Expressions, characteristic features, customs, habits, ways of thinking, feeling, prejudices, ethical, religious concepts and psychosocial risks must be total or partially to the influence of the environment, whose negative aspects should be improved through the implementation of corrective and preventive actions, avoiding its recurrence. The lack of research on the psychosocial risks in companies affects workers not only in relations work, but also on a personal level, the purpose being pursued with this research is to counter the main risk factors psychosocial affecting the normal performance activities of the workers at NOVACERO S.A. industrial plant in the area of recycling.